2013
DOI: 10.1108/17506121311315391
|View full text |Cite
|
Sign up to set email alerts
|

Physician Medicare fraud: characteristics and consequences

Abstract: PurposeCriminal Medicare and/or Medicaid fraud costs taxpayers $60‐250 billion annually. This paper aims to outline the characteristics of physicians who have been convicted of such fraud.Design/methodology/approachThe names of convicted physicians were first gathered from public databases (primarily, the OIG exclusion list). The names were further cross‐checked and verified with other public records. Details regarding demographics and the particulars of the fraud were obtained by searching court documents, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 13 publications
7
35
0
Order By: Relevance
“…Nortjé and Hoffmann's [12] study found that fraudulent activities committed by SA healthcare professionals consisted mainly of billing for false claims, which are similar to the findings of this study. Syndicate fraud committed through identity theft and the submission of fictitious claims was identified in this study, which is in line with the findings of Flynn, [10] Pande and Maas [20] and Nortjé and Hoffmann. [12] Our study also found that unlicensed people pose as healthcare service providers.…”
Section: Discussionsupporting
confidence: 90%
“…Nortjé and Hoffmann's [12] study found that fraudulent activities committed by SA healthcare professionals consisted mainly of billing for false claims, which are similar to the findings of this study. Syndicate fraud committed through identity theft and the submission of fictitious claims was identified in this study, which is in line with the findings of Flynn, [10] Pande and Maas [20] and Nortjé and Hoffmann. [12] Our study also found that unlicensed people pose as healthcare service providers.…”
Section: Discussionsupporting
confidence: 90%
“…Criminal cases were examined in 2/32 studies [ 36 , 37 ]; both found that male doctors were significantly more likely to experience criminal charges ( P <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 27/32 studies found that male doctors were more likely to have had experienced at least one medico-legal action [ 5 7 , 13 , 14 , 16 – 19 , 21 23 , 25 28 , 30 , 32 – 39 ], although 4/27 studies did not calculate inferential statistics and did not provide sufficient data to enable the calculation of any effect size [ 13 , 18 , 32 , 38 ]. Of the studies that provided an effect size or where it was possible to calculate an effect size from the data reported, 22/23 demonstrated that male doctors were statistically significantly more likely to have had experienced a medico-legal action ( P ≤0.05) [ 5 7 , 14 , 16 , 17 , 19 23 , 25 28 , 30 , 31 , 33 37 , 39 ]. The remaining study examined doctors at two separate time intervals finding a significant association at the early time point only [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OIG has authority to exclude individuals and entities from federally funded healthcare programs, such as Medicare. Unfortunately, the LEIE is not all-inclusive where 38% of providers with fraud convictions continue to practice medicine and 21% were not suspended from medical practice despite their convictions [51]. Moreover, the LEIE dataset only contains the NPI values for a small percentage of physicians and entities.…”
Section: Leiementioning
confidence: 99%